2001
DOI: 10.1128/jb.183.24.7213-7223.2001
|View full text |Cite
|
Sign up to set email alerts
|

Complex Regulatory Network Controls Initial Adhesion and Biofilm Formation in Escherichia coli via Regulation of the csgD Gene

Abstract: The Escherichia coli OmpR/EnvZ two-component regulatory system, which senses environmental osmolarity, also regulates biofilm formation. Up mutations in the ompR gene, such as the ompR234 mutation, stimulate laboratory strains of E. coli to grow as a biofilm community rather than in a planktonic state. In this report, we show that the OmpR234 protein promotes biofilm formation by binding the csgD promoter region and stimulating its transcription. The csgD gene encodes the transcription regulator CsgD, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
309
0
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 365 publications
(333 citation statements)
references
References 54 publications
(52 reference statements)
17
309
0
7
Order By: Relevance
“…Similarly, maturation conditions were defined to allow rapid biofilm development. Initial experiments investigating maturation of natural E. coli PHL644 biofilms in M63 (minimal) and 1× and ½×LB (rich) media at 30 °C and 37 °C found that the lower temperature and minimal medium gave higher surface coverage and enhanced development of three-dimensional biofilm structure, as previously suggested by [25]. Spin-coating E. coli onto the solid substrate removed the need for initial attachment and monolayer formation, but the growth conditions chosen were designed to promoter later stages of biofilm development.…”
Section: Formation Of Scebsmentioning
confidence: 89%
See 2 more Smart Citations
“…Similarly, maturation conditions were defined to allow rapid biofilm development. Initial experiments investigating maturation of natural E. coli PHL644 biofilms in M63 (minimal) and 1× and ½×LB (rich) media at 30 °C and 37 °C found that the lower temperature and minimal medium gave higher surface coverage and enhanced development of three-dimensional biofilm structure, as previously suggested by [25]. Spin-coating E. coli onto the solid substrate removed the need for initial attachment and monolayer formation, but the growth conditions chosen were designed to promoter later stages of biofilm development.…”
Section: Formation Of Scebsmentioning
confidence: 89%
“…The present work is focused on E. coli K-12 strain PHL644 [24], which readily generates curli and displays a hyperadhesive phenotype. Curli are extracellular protein fibres that have been shown to mediate adhesion, colonisation, and biofilm formation [25][26][27]. This strain carries a mutation in the osmolarity-responsive response regulator OmpR (ompR234) which leads to increased activation of csgD expression.…”
Section: Formation Of Scebsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cette observation confirme que la formation des micro-colonies est bien un méca-nisme d'agrégation cellulaire qui nécessite une mobilité, et non pas seulement une croissance clonale à partir d'une cellule bactérienne donnée. Chez d'autres organismes, comme Escherichia coli, il a été montré que des appendices extracellulaires comme les fimbriae [10] ou les « curli » [11] sont également importants lors de la formation du biofilm. En utilisant le type de criblage décrit par O'Toole et Kolter, mais en modifiant légèrement les conditions de croissance, nous avons pu identifier chez P. aeruginosa de nouveaux facteurs d'attachement [8].…”
Section: Souches Adhérentesunclassified
“…On a évoqué le cas du quorum sensing, de Crc, mais d'autres études ont également montré que GacA, le régulateur de réponse du couple GacA/GacS, un système à deux composants, influe égale-ment sur la formation du biofilm [22]. Chez E. coli, les systèmes à deux composants EnvZ/OmpR et CpxA/CpxR, permettent de percevoir des stress au niveau de l'enveloppe bactérienne, et seraient impliqués conjointement dans la formation du biofilm [11,23]. La variation de phase est une stratégie qui permet à la bactérie de s'adapter rapidement à des variations de conditions environnementales.…”
Section: -Oxo-c12-hslunclassified